Testamentary Capacity and the Bequeathable Third in the Islamic Law of Wills: Amanullah bin Haji Ali Hassan v. Hajjah binti Sheik Madar - Balan, P (Journal of Malaysian and Comparative Law, 2018)
Muslim Law – Amanullah bin Haji Ali Hassan v. Hajjah binti Sheik Madar